Advanced Multi-Watermarking For Medical Images - Sunil Kumar Vishwakarma, Birendra Kumar Sharma, Syed Qamar Abbas, (Design Engineering, 2021)
Multi-layer watermarking is used for detecting the tampering and authentication of ownership. This watermarking method represents the combination of stationary wavelet transform and singular value decomposition. Will be implemented in different medical images with a various type of attacks for detecting the tamper ness. Proposed method mainly focuses on the two watermark medical data images and binary logo images both of different sizes same as that of cover image to achieve the high capacity. Peak signal-to-noise ratio is obtained through this method is comparable higher than the other similar techniques. Normalize Cross correlation values establish this scheme which performs better than other techniques of robustness. The technique is proved to be much balanced PSNR and NCC values which do not differ much among various modalities of images. The Vulnerability of the watermark help to detect tampers.